Estudo teórico e experimental do processo de secagem do abacate (Persea americana Mill) - Alves, Suerda Bezerra (2014)
The avocado is a fruit known for its high fat contained in the pulp and like most agricultural products also features a high moisture content in your composition. Drying of the avocado is important since the use of the fruit is performed to obtain a product of greater value, for example, oil serving as a raw material for biodiesel production. This research was developed with the aim to contribute to the theoretical and experimental study of convection drying process of hot air to the avocado in nature, through experimental analysis, mathematical models in the literature and reported an increase of new equations. For the drying process a convective dryer was used, operating in the temperature range of temperature (40, 50, 60 and 70)°C. The geometry of the samples and the flow rate of the drying air were considered constant. For the isotherm Desorption was used a temperature range between was (40, 50, 60, 70, 80 and 90)°C. The validation of the models used in this research was performed by the method of least squares, in possession of the experimental data the kinetic and the desorption isotherms for the avocado in nature. The experimental results of drying kinetics were expressed by models that predict moisture loss through convective mass coefficient and the effective mass diffusivity. The loss of mass on the surface of avocado was expressed by Newton law of cooling, while the inside was expressed by the empirical models represented by Page and Modified. For desorption isotherms the experimental results were demonstrated using models that predict the equilibrium moisture content obtained experimentally in relation to the activity of pre-established water. The desorption isotherm avocado in nature was expressed by the empirical models and Copace amd Sigma-copace. We also developed new mathematical models to represent the kinetic and isotherm avocado in nature.